An X/Ku band phase shifter with filter compensation technology. Issue 2 (16th January 2023) - Zeng, Jialong; Yu, Zhongjun; Yuan, Yang; Li, Jiaxuan; Zhang, Desheng
Abstract: This letter proposes an ultra‐wideband switched T‐type phase shifter, which covers the whole X/Ku band. The proposed switched T‐type phase shifter integrates a switched filter compensation structure, achieving a flat relative phase shift in broadband, which the conventional one cannot acquire. In addition, the designed T‐type phase shifter can further reduce the phase error and improve the phase shift capability with a phase shift greater than 45°. Employing the proposed architecture, a 90° T‐type phase shifter is designed and fabricated in 0.15‐μm GaAs pHEMT process. The measured results show that the proposed T‐type phase shifter achieves a stable 90° phase shift at 8 to 18 GHz with a phase error of less than ±2°, and an insertion loss (IL) of 2.4 to 4.2 dB. And the chip size of the switched T‐type phase shifter is 0.62 × 0.75 mm 2 . Thanks to its good performance, the proposed T‐type phase shifter is very suitable for various radar and satellite communication systems. Abstract : This letter proposes an ultra‐wideband switched T‐type phase shifter, which covers the whole X/Ku band. The proposed switched T‐type phase shifter integrates a switched filter compensation structure, achieving a flat relative phase shift in broadband, which the conventional one cannot acquire. In addition, the designed T‐type phase shifter can further reduce the phase error and improve the phase shift capability with a phase shift greater than 45°.